Earthquake-induced liquefaction around marine structures - Sumer, B. Mutlu; Ansal, Atilla; Cetin, K. Onder; Damgaard, Jesper; Gunbak, A. Riza; Hansen, Niels-Erik Ottesen; Sawicki, Andrzej; Synolakis, Costas E.; Yalciner, Ahmet Cevdet; Yuksel, Yalcin; Zen, Kouki (ASCE-AMER SOC CIVIL ENGINEERS, 2007)
This paper gives a state-of-the-art review of seismic-induced liquefaction with special reference to marine structures. The paper is organized in seven sections: (1) introduction; (2) seismic-induced liquefaction in which a general account of soil liquefaction is presented; (3) existing codes/guidelines regarding seismic-induced liquefaction and its implications for marine structures; (4) review of the Japanese experience, giving a brief history of earthquakes and design codes, describing the current design code/standard for port and harbor facilities including counter measures and remediation; (5) review of the liquefaction damage inflicted on marine structures in the 1999 Turkey Kocaeli Earthquake, including recommendations which draw on the lessons learned; (6) assessment of postliquefaction ground deformation (more specifically of lateral ground spreading); and (7) tsunamis and their impact. The present paper and the existing guidelines (CEN, ASCE, and PIANC) form a complementary source of information on earthquake-induced liquefaction with special reference to its impact on marine structures.
Keywords: coastal structures; earthquakes; guidelines; liquefaction; offshore structures; seismic effects; MODEL; TSUNAMI; WAVES; PREDICTION; RESISTANCE; AMPLITUDE; MARMARA; FLOW; SEA; Engineering; Water Resources